CD33 Delineates Two Functionally Distinct NK Cell Populations Divergent in Cytokine Production and Antibody-Mediated Cellular Cytotoxicity - Hejazi, Maryam; Zhang, Congcong; Bennstein, Sabrina B.; Balz, Vera; Reusing, Sarah B.; Quadflieg, Melissa; Hoerster, Keven; Heinrichs, Stefan; Hanenberg, Helmut; Oberbeck, Sebastian; Nitsche, Marcus; Cramer, Sophie; et al. (Frontiers in Immunology, 2022)
The generation and expansion of functionally competent NK cells in vitro is of great interest for their application in immunotherapy of cancer. Since CD33 constitutes a promising target for immunotherapy of myeloid malignancies, NK cells expressing a CD33-specific chimeric antigen receptor (CAR) were generated. Unexpectedly, we noted that CD33-CAR NK cells could not be efficiently expanded in vitro due to a fratricide-like process in which CD33-CAR NK cells killed other CD33-CAR NK cells that had upregulated CD33 in culture. This upregulation was dependent on the stimulation protocol and encompassed up to 50% of NK cells including CD56dim NK cells that do generally not express CD33 in vivo. RNAseq analysis revealed that upregulation of CD33+ NK cells was accompanied by a unique transcriptional signature combining features of canonical CD56bright (CD117high, CD16low) and CD56dim NK cells (high expression of granzyme B and perforin). CD33+ NK cells exhibited significantly higher mobilization of cytotoxic granula and comparable levels of cytotoxicity against different leukemic target cells compared to the CD33- subset. Moreover, CD33+ NK cells showed superior production of IFN𝛾 and TNF𝜶, whereas CD33- NK cells exerted increased antibody-dependent cellular cytotoxicity (ADCC). In summary, the study delineates a novel functional divergence between NK cell subsets upon in vitro stimulation that is marked by CD33 expression. By choosing suitable stimulation protocols it is possible to preferentially generate CD33+ NK cells combining efficient target cell killing and cytokine production, or alternatively CD33- NK cells, which produce less cytokines but are more efficient in ADCC applications.